β-Diketiminate complexes of group 13 elements and their use in small molecule activation and catalysis - Caise, A (2019)
This thesis examines the potential of hydrides of the group 13 metals aluminium and gallium to function as homogeneous catalysts for the reduction of unsaturated substrates including CO2, aldehydes and ketones. In addition, it reports on studies designed to probe the mechanisms by which these processes occur. Chapter 3 details the preparation of a series of novel β-diketiminate (or Nacnac) ligated aluminium hydrides of the form {HC(XCNDipp)2}Al(R)H {X = Me, NMe2; (DippNacnac)Al(R)H}, which differ in the nature of the auxiliary R substituent and the Nacnac backbone itself. These systems show considerable variation in the nature of the Al-H bond and significant differences in reactivity with respect to the hydroalumination of carbon dioxide. Electron-donating R substituents give rise to weaker and more hydridic Al-H bonds, which exhibit enhanced rates of insertion of the CO2 molecule. The treatment of the resulting κ1-formate complexes with B-H containing reductants under stoichiometric and catalytic conditions reveals that no Al-O/B-H metathesis occurs, even under forcing conditions. This study did however lead to the isolation of a range of novel boryloxy complexes, (DippNacnac)Al(R)(OBXX’) (X = X’ = cat, 9-BBN; X = H, X’ = OMe) and borohydride complexes (DippNacnac)Al(R)(H2BX2) (X2 = (9-BBN), H2). It is concluded that no catalytic turnover can be achieved in the reduction of CO2 by boranes mediated by these aluminium hydrides, presumably due to the excessive strength of the Al-O bond, and the consequent lack of viability of Al-O/B-H metathesis. Chapter 4 describes a number of synthetic routes for the preparation of unsymmetrically substituted Nacnac-ligated gallium monohydride complexes, including a rare example of a base-stabilised cationic gallium hydride. The range of novel hydrides reported offers variation in the steric and electronic properties of the auxiliary R substituent. Studies of stoichiometric reactivity reveal that, as with related alanes, gallium hydrides which bear more σ-donating R substituents are more amenable to the hydrogallation of CO2. In addition, studies were undertaken to establish the impact of both the gallium-bound R substituent and the borane on Ga-O/B-H metathesis processes leading to the regeneration of a Ga-H bond from the corresponding formate complex {HC(MeCNDipp)2}Ga(R)(OC(O)H), [Dipp1]Ga(R)(OC(O)H). With the factors influencing both the insertion and metathesis processes established, the ability of these Nacnac gallium hydrides to catalyse the borane-mediated reduction of CO2 was then investigated. The work presented in Chapter 5 demonstrates that the Nacnac-ligated gallium hydride complex, [Dipp1]Ga(Ad)H, can be employed in tandem with B(C6F5)3 to effect the catalytic hydrosilylation of CO2. Whilst forcing conditions are required to bring about catalytic turnover (and only modest TOF values can be achieved), this system represents a rare example of a main group hydride catalyst for this process. In addition, it can be shown that selectivity can be controlled through the ratio of Lewis acid co-catalyst employed. A series of mechanistic studies is described which shows that the B(C6F5)3 co-catalyst leads to the activation of the gallium complex towards both processes (insertion, metathesis) that are key to catalytic turnover. During the course of this study, the first examples of three-coordinate β-diketiminate-ligated gallium cations were synthesised. Chapter 6 describes a study of the mechanisms of the reduction of organic carbonyl substrates, mediated by aluminium and gallium hydrides. It is demonstrated that the hydrogallation of aldehydes by β-diketiminate-ligated gallium hydrides is relatively limited and only one gallium hydride of this nature, [Dipp1]GaH2, could be found to hydrogallate benzaldehyde, requiring forcing conditions to bring about such reactivity. However, the gallium alkoxide product so generated is amenable to rapid Ga-O/B-H metathesis to regenerate a Ga-H bond and release the reduced organic product. Thus, in accordance with the research reported in Chapters 4 and 5, the hydroboration of C=O bonds can be effected by gallium systems based on an inner-sphere mechanism involving insertion and Ga-O/B-H metathesis steps. By contrast, a wide range of β-diketiminate-ligated aluminium hydrides can be shown to hydroaluminate benzaldehyde under ambient conditions. However, in this case the resulting metal alkoxides are resolutely unreactive towards B-H containing reagents. This behaviour is consistent with the reactivity towards CO2 reported in Chapter 3 and can be rationalized by the underlying thermodynamics of Al-O/B-H metathesis (which are unfavourable). Nonetheless, literature reports of the catalytic hydroboration of benzaldehyde by aluminium hydrides are confirmed to be correct – and a series of mechanisms based on outer-sphere processes which avoid ‘net cleavage’ of the Al-O bond have therefore been investigated.